Pengaruh Pemilihan Kepala Daerah Terhadap Pasar Tenaga Kerja: Analisis Sektor Formal Dan Informal Level Kabupaten/Kota Di Pulau Jawa - Gunawan, Beni Teguh (Jurnal Kajian Ekonomi dan Keuangan, 2018)
Local election (pilkada) become a political phenomenon impact to various other sectors, not least the economic sector. Local elections in Indonesia are conducted at district and provincial levels. The incumbent candidate will use their power to control the fiscal sector in the region to improve their electability. One of the effort is to improve performance of the regional economy that will impact on the new job creation as the trade-off concept in the Phillips curve. Empirical results indicate that district/municipal election significantly influences the absorption of informal sector workers. A year before the district-level elections, an increase of informal sector workers by 3.39%, in the other hand, it reduces formal sector employment by 5.54%. Different results are shown in the provincial elections, where one year before the pilkada has no impact on the formal sector. When district/municipal and provincial elections are held in the same year, the absorption of informal sector workers decreased by 4.77% while the formal sector increased by 8.28%. When the incumbent candidate participate the next election, the informal workers increase 6.58% while formal employment does not affected.